Gerenciamento de materiais recicláveis por associação de catadores no cenário socioambiental de Curitiba-PR - Fernandez, Judith Karina Agudelo (2019)
The present study deals with the management of recyclable materials by an association of garbage collectors of Curitiba city, Paraná, Brazil. It is part of public policies to reduce socioenvironmental and economic impacts of municipal solid waste. The objective is to examine the relevance of the principals of classical administration in the association management of garbage collectors in Curitiba city, linked to the Ecocidadão Program of the Municipal Environment Secretariat (SMMA). The public policy goals is poor people inclusion and socio-environmental and economic reduction of waste impacts. According to law number 12.305/2010, which mentions the National Policy for Solid Waste (PNRS), the garbage collectors must be incorporated into solid waste residues collection process. Governmental goals are mainly to avoid the disposal of dumps in the open air, and to emancipate lowincome people through a fair work. In this sense, it is up to the garbage collectors to think freely about the organization of the activities in a suitable space. The study approaches fundamentally are qualitative, and the data collection came from interviews and observations. The information was recorded and organized in a systematic structure in a particularly community. There was no intention to change the reality, and the researcher participated of the Association daily work (Acuba) as an observer. The conceptual study framework was based on the classical administrative theory, compiled by Henry Fayol. This theoretical body emphasizes organizational structure as the key to work efficiency. The hypothesis of the dissertation is that in the organizational structure of the Associations of garbage collectors, that separate recycle material, it is essential to have a hierarchy, authority, centrality, and unity of direction. The analysis does not allow the creation of representative models applicable to other similar spaces maintained in Curitiba. In daily Acuba routine, it was not possible to detected authority, and autonomy actions, and possibilities to gain emancipation. The president and councilors are not seen as authorities for the others Acuba workers. Even though they have elections and hierarchy, the responsibilities are divided with little clarity, and the different functions are shared. In the other hand, all garbage collectors follow the SMMA principles, registered in documents, and they understand that the municipal policy is the main authority.